2023
DOI: 10.3389/fpls.2023.1154169
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis of molecular mechanisms underlying adventitious root developments in Huangshan Bitter tea (Camellia gymnogyna Chang) under red light quality

Abstract: As the formation of adventitious roots (AR) is an important component of in vitro regeneration of tea plants, the propagation and preservation of Huangshan Bitter tea (Camellia gymnogyna Chang) cuttings have been hindered due to its lower rooting rate. As light is a crucial environmental factor that affects AR formation, this study aimed to investigate the special role of red light (RL) in the formation of AR in Huangshan Bitter tea plants, which has not been well understood. Huangshan Bitter tea plants were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…AR numbers and IAA contents increase in OsYUCCA1 -overexpressing rice plants, whereas AR numbers decrease in plants subjected to OsYUCCA1 antisense treatment ( Yamamoto et al., 2007 ). DEGs related to plant hormone pathways show significant changes in bitter tea ARs subjected to different light treatments, corresponding to increases in IAA, ZT, and GA 3 contents and decreases in ABA contents during AR formation ( Fu et al., 2023 ). A total of seven types of phytohormones, including ABA, auxin, BRs, cytokinins, ET, GAs, and JA, are involved in poplar AR formation ( Zhang et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…AR numbers and IAA contents increase in OsYUCCA1 -overexpressing rice plants, whereas AR numbers decrease in plants subjected to OsYUCCA1 antisense treatment ( Yamamoto et al., 2007 ). DEGs related to plant hormone pathways show significant changes in bitter tea ARs subjected to different light treatments, corresponding to increases in IAA, ZT, and GA 3 contents and decreases in ABA contents during AR formation ( Fu et al., 2023 ). A total of seven types of phytohormones, including ABA, auxin, BRs, cytokinins, ET, GAs, and JA, are involved in poplar AR formation ( Zhang et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most prevalent rooting type found in tea plants is the comprehensive rooting type, and the level of difficulty in rooting is typically associated with the proportions of callus rooting and cortex rooting types, which may cause the difference in rooting ability of various varieties. Nowadays, many studies have focused on the mechanisms of AR formation in tea plants, and preliminary results all showed that auxin is a key factor involved in this process ( Wang et al., 2022b ; Fu et al., 2023 ; Hu et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%